Aldehyde hydrogenation catalyst and method for preparing the same

CN118122332BActive Publication Date: 2026-10-23PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211437749.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2026-10-23
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

[0007]中国专利CN105727959B公布了一种利用微通道反应器制备甲醇合成催化剂的方法,该方法利用微通道反应器在共沉淀法制备催化剂材料方面的优势,实现了Cu、Zn、Al三元沉淀的连续化制备,但该工艺使用单一微通道反应器,三元金属的沉淀同时进行,不利于Cu的高分散

Benefits of technology

[0022]本发明所公开的制备方法得到的催化剂具有高的重质醛转化率:制备过程在微通道反应器内进行,在第一个微通道反应器内通过加入晶化剂实现铝、锌、硅盐的预晶化,第二个微通道反应器内实现铜、锌盐的老化沉淀,通过预晶化与共沉淀结合的工艺,提高了催化剂的比表面积,有利于铜在载体表面的分散,进而有利于提高重质醛的催化转化效率,同时通过过滤液的循环利用,减少了废水排放,降低了催化剂制备成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118122332B_ABST
    Figure CN118122332B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of an aldehyde hydrogenation catalyst, characterized by comprising the following steps: (1) mixing an aluminum nitrate solution, a zinc nitrate solution, a silica sol and a deionized water solution, adding ethylenediamine and triethylene glycol into the deionized water solution to prepare a pre-crystallization solution, pumping the mixed solution and the pre-crystallization solution into the inlets of first micro-channel reactors respectively, and obtaining a precursor solution A through mixed crystallization; (2) pumping a copper nitrate solution, a zinc nitrate solution, the precursor solution A and a precipitator into the inlets of micro-reactors B respectively to carry out co-precipitation, and obtaining an aging solution B through mixing; (3) filtering the aging solution, recycling the filtered solution into a second micro-channel reactor, and carrying out washing, drying and catalyst forming on the filter cake.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical catalyst preparation technology, specifically relating to an aldehyde hydrogenation catalyst prepared using a microchannel reactor and its preparation method. Background Technology

[0002] Currently, the catalysts used in gas-phase aldehyde hydrogenation are mainly copper-zinc (Cu-Zn) catalysts, which are characterized by low pollution, long lifespan, and high mechanical strength. In Cu-Zn catalysts, copper is the active component, while ZnO acts as a support and promoter. Cu-Zn catalysts are generally prepared using a co-precipitation method, and the resulting metal oxide powder is pressed into cylindrical catalysts. Aluminum is frequently used as a promoter, and the Al2O3 content in the catalyst is generally between 1% and 10%. The gas-phase aldehyde hydrogenation catalysts used domestically are all Cu-Zn catalysts, prepared using the co-precipitation method, and formed by pressing. These catalysts are mainly used in the hydrogenation of butyraldehyde and octenal. The key to preparing this catalyst using the co-precipitation method is improving the dispersion of copper.

[0003] Chinese patent CN 105080549B discloses a catalyst for the gas-phase hydrogenation of octenal to 2-ethylhexanol and its preparation method. A stepwise precipitation method is employed, and modification is used to improve the catalyst's activity and selectivity. However, the catalyst exhibits low conversion and selectivity for 2-propyl-2-heptanal in the evaluation.

[0004] Chinese patent CN 100398202C discloses a catalyst for the gas-phase hydrogenation of aldehydes and its preparation method. The catalyst is prepared by a continuous co-precipitation method using a mixed solution of copper, zinc, and aluminum nitrates. The resulting catalyst exhibits high low-temperature activity, selectivity, and stability when used for the hydrogenation of butyraldehyde and octenal. However, the selectivity of this catalyst is relatively low when used for the hydrogenation of 2-propyl-2-heptal.

[0005] Chinese patent CN102350360A discloses a highly liquid-resistant aldehyde hydrogenation catalyst proposed by the Nanjing Chemical Research Institute of Sinopec. The preparation method employs a secondary calcination process to improve the catalyst's resistance to immersion. While this process enhances the catalyst's resistance to immersion, the secondary calcination reduces the catalyst's specific surface area and pore volume.

[0006] Chinese patent CN108043411A discloses a catalyst and its preparation method for the hydrogenation of n-butyraldehyde to n-butanol by Yantai Wanhua Chemical. The catalyst comprises copper oxide, zinc oxide, and silicon dioxide. The catalyst is prepared using a simultaneous precipitation method, where copper and zinc are precipitated at two different temperatures to obtain two different pore structures, forming a dual-pore system.

[0007] Chinese patent CN105727959B discloses a method for preparing methanol synthesis catalysts using a microchannel reactor. This method utilizes the advantages of microchannel reactors in the co-precipitation method for preparing catalyst materials to achieve continuous preparation of Cu, Zn, and Al ternary precipitates. However, this process uses a single microchannel reactor, and the precipitation of the ternary metals occurs simultaneously, which is not conducive to the high dispersion of Cu. Summary of the Invention

[0008] In view of the defects of the above-mentioned technology, the purpose of this invention is to improve the catalytic conversion rate and selectivity of heavy aldehydes. The preparation process is carried out in a microchannel reactor. In the first microchannel reactor, aluminum, zinc and silicon salts are pre-crystallized by adding a crystallizing agent. In the second microchannel reactor, copper and zinc salts are aged and precipitated. By combining pre-crystallization and co-precipitation, the specific surface area of ​​the catalyst is increased, which is beneficial to the dispersion of copper on the carrier surface, thereby improving the catalytic conversion efficiency of heavy aldehydes. At the same time, the recycling of the filtrate reduces wastewater discharge and lowers the catalyst preparation cost.

[0009] The present invention employs a method for preparing an aldehyde hydrogenation catalyst, comprising the following steps:

[0010] (1) A mixture of aluminum nitrate, zinc nitrate, silica sol, and deionized water was prepared, and ethylenediamine and triethylene glycol were added to deionized water to prepare a pre-crystallization solution. The mixture and the pre-crystallization solution were pumped into the inlet of the first microchannel reactor, and the precursor solution A was obtained by mixing and crystallizing.

[0011] (2) Co-precipitate the mixed solution of copper nitrate and zinc nitrate, precursor solution A and precipitant into the inlet of microreactor B respectively, and then mix them to obtain aging solution B;

[0012] (3) The aging liquid is filtered, and the filtered solution is recycled back to the second microchannel reactor. The filter cake is washed, dried, and the catalyst is formed.

[0013] The catalyst preparation process of the present invention is carried out in a microchannel reactor. In the first microchannel reactor, aluminum, zinc and silicon salts are pre-crystallized by adding a crystallizing agent, and copper and zinc salts are aged and precipitated in the second microchannel reactor. The combination of pre-crystallization and co-precipitation improves the dispersion of copper on the support surface, thereby improving the catalytic conversion efficiency of heavy aldehydes. At the same time, the recycling of the filtrate reduces wastewater discharge and lowers the catalyst preparation cost.

[0014] Preferably, in the preparation method of the present invention, in step (1), the mixed crystallization temperature is 75-8°C and the pH of the precursor solution is 7-8.

[0015] Preferably, in the preparation method of the present invention, in step (2), the neutralization temperature is controlled at around 80°C and the pH of the aging solution is 7-8.

[0016] Preferably, in the preparation method of the present invention, in step (3), the washing conditions are: the filter cake is washed with deionized water at 40-50°C; the drying conditions are: calcined at 360-400°C for 4-5 hours; and the molding conditions are: graphite is added and pressed into tablets to obtain the catalyst.

[0017] Preferably, the method of the present invention is carried out in at least two microchannel reactors in series.

[0018] Preferably, in the preparation method of the present invention, in step (3), the filtrate at the outlet of the second reactor is recycled back to the inlet of the second reactor.

[0019] The present invention also provides an aldehyde hydrogenation catalyst prepared by the preparation method according to claims 1-6, characterized in that the catalyst comprises the following substances in weight percentage: copper oxide 10%-50%, copper 5%-30%, zinc oxide 30%-80%, zinc 5%-20%, aluminum oxide 0.1%-10%, graphite 1%-3%, and silicon oxide 0.1%-20%.

[0020] Preferably, the aldehyde hydrogenation catalyst of the present invention is characterized in that the catalyst has the following main components by mass: 20% to 40% copper oxide, 45% to 70% zinc oxide, 0.1% to 6% aluminum oxide, 1% to 3% graphite, and 0.1% to 10% silicon oxide.

[0021] The beneficial effects of this invention are:

[0022] The catalyst prepared by the method disclosed in this invention has a high conversion rate of heavy aldehydes: the preparation process is carried out in a microchannel reactor. In the first microchannel reactor, aluminum, zinc and silicon salts are pre-crystallized by adding a crystallizing agent, and copper and zinc salts are aged and precipitated in the second microchannel reactor. The combination of pre-crystallization and co-precipitation increases the specific surface area of ​​the catalyst, which is beneficial to the dispersion of copper on the support surface, thereby improving the catalytic conversion efficiency of heavy aldehydes. At the same time, the recycling of the filtrate reduces wastewater discharge and lowers the catalyst preparation cost. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the process flow for co-precipitation in a microchannel reactor. Detailed Implementation

[0024] The following provides a detailed description of the embodiments of the present invention: These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and processes. However, the scope of protection of the present invention is not limited to the following embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions.

[0025] Unless otherwise specified, the experimental methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and compounds are commercially available.

[0026] The apparatus and analytical methods used in the experiment: A self-assembled microchannel reactor was used in the catalyst preparation process, with microchannel reactor A having an equivalent diameter of 6 mm and microchannel reactor B having an equivalent diameter of 15 mm. Hydrogenation evaluation was performed using a 300 mL fixed-bed apparatus under the following reduction conditions: hydrogen reduction, reduction temperature 190℃, and reduction time 6 hours. Specific implementation examples:

[0028] Example 1

[0029] (1) Prepare 2000ml of aluminum-zinc-silicon mixed solution by mixing 100g aluminum nitrate, 100g zinc nitrate and 60g silica sol. Add 120g ethylenediamine and 200g triethylene glycol to deionized water to prepare a precrystallization solution. Pump the aluminum-zinc-silicon mixed solution and the precrystallization solution into the inlet of microreactor A by weight respectively. After mixing, the precursor solution A1 is obtained. Control the temperature of microreactor A at about 80℃ and adjust the pH of the solution to 7-8.

[0030] (2) Prepare 13000 ml of copper-zinc mixed solution by mixing 1170 g of copper nitrate and 1000 g of zinc nitrate. Pump the mixed solution, precursor solution A1 and precipitant into the inlet of microreactor B respectively. After mixing, aging solution B1 is obtained. Control the neutralization temperature to about 80℃ and adjust the solution pH to 7-8.

[0031] (3) The aging solution B is filtered, and the filtrate is returned to the microreactor B. The filter cake is washed with deionized water at 40-50°C. After drying, the obtained filter cake is calcined at 360-400°C for 4-5 hours. Then, 2% of the total mass of the obtained material is added to graphite and pressed into tablets to obtain catalyst CA-1. Example 2

[0032] (1) Prepare 2000ml of aluminum-zinc-silicon mixed solution by mixing 150g aluminum nitrate, 135g zinc nitrate and 580g silica sol. Add 150g ethylenediamine and 260g triethylene glycol to deionized water to prepare a pre-crystallization solution. Pump the aluminum-zinc-silicon mixed solution and sodium carbonate solution with a weight percentage of 20% into the inlet of microreactor A respectively. After mixing and aging, the precursor solution A2 is obtained. Control the temperature of microreactor A at about 80℃ and adjust the pH of the solution to 7-8.

[0033] (2) Prepare 13000 ml of copper-zinc mixed solution by mixing 1250 g of copper nitrate and 1000 g of zinc nitrate. Pump the mixed solution, precursor solution A2 and precipitant into the inlet of microreactor B respectively. After mixing, aging solution B2 is obtained. Control the neutralization temperature at about 80℃ and adjust the solution pH to 7-8.

[0034] (3) Filter the aging liquid B, return the filtrate to the microreactor B, wash the filter cake with deionized water at 40-50℃, dry the obtained filter cake, calcine it at 360-400℃ for 4-5 hours, add the filter cake obtained in step (2), mix evenly, and then add 2% of the total mass of the obtained substances to form graphite tablets to obtain catalyst CA-2.

[0035] Example 3

[0036] (1) Prepare 2000ml of aluminum-zinc-silicon mixed solution by mixing 130g aluminum nitrate, 150g zinc nitrate and 780g silica sol. Add 140g ethylenediamine and 270g triethylene glycol to deionized water to prepare a pre-crystallization solution. Pump the aluminum-zinc-silicon mixed solution and sodium carbonate solution with a weight percentage of 20% into the inlet of microreactor A respectively. After mixing and aging, the precursor solution A3 is obtained. Control the temperature of microreactor A at about 80℃ and adjust the pH of the solution to 7-8.

[0037] (2) Prepare 1300ml of copper-zinc mixed solution by mixing 1300g of copper nitrate and 1300g of zinc nitrate. Pump the mixed solution, precursor solution A3 and precipitant into the inlet of microreactor B respectively. After mixing, aging solution B3 is obtained. Control the neutralization temperature at about 80℃ and adjust the solution pH to 7-8.

[0038] (3) Filter the aging liquid B, return the filtrate to the microreactor B, wash the filter cake with deionized water at 40-50℃, dry the obtained filter cake, calcine it at 360-400℃ for 4-5 hours, add the filter cake obtained in step (2), mix evenly, and then add 2% of the total mass of the obtained substances to form graphite tablets to obtain catalyst CA-3.

[0039] Comparative Example 1

[0040] (1) Prepare 1300ml of copper-zinc mixed solution by mixing 117g of copper nitrate and 210g of zinc nitrate, and prepare 200ml of aluminum-zinc-silicon mixed solution by mixing 10g of aluminum nitrate and 10g of zinc nitrate. Add the aluminum-zinc-silicon mixed solution and sodium carbonate solution with a weight percentage of 20% in parallel to a neutralization tank with heat preservation and stirring for aging. Control the neutralization temperature at about 80℃ and adjust the pH of the solution to 7-8.

[0041] (2) Add the copper-zinc mixed solution and the sodium carbonate solution with a weight percentage of 20% to the same tank in parallel flow, neutralize and age under stirring, and adjust the pH of the solution to 7-8 with sodium carbonate;

[0042] (3) Wash with deionized water at 40-50℃, dry the obtained filter cake, calcine at 360-400℃ for 4-5 hours, and then add 2% of the total mass of the obtained material to form a graphite tablet to obtain catalyst CB-1.

[0043] Comparative Example 2

[0044] This example was prepared using the method described in Chinese Patent CN 105080549B.

[0045] 4 L of a prepared 1 mol / L sodium carbonate solution was placed in a stirred sedimentation tank. 55 g of silica sol was added dropwise to the alkaline solution at 60 °C. The mixture was aged at 65 °C for 20 minutes. 1000 ml of 1 mol / L copper nitrate solution, 1773 ml of 1 mol / L zinc nitrate solution, and 100 ml of 1 mol / L aluminum nitrate solution were prepared to form a mixed solution A. Solution A was added to the above solution at a uniform rate. The neutralization time was 30 minutes. The mixture was then stirred and aged at 70 °C for 30 minutes. After concentration and washing, the filter cake was obtained by pressure filtration, dried, and 0.5 g of modifying agent was added. The granules were then calcined at 320 °C for 2 hours and then pressed into tablets to obtain the reference catalyst sample CB-2.

[0046] Comparative Example 3

[0047] This example uses the method described in Chinese Patent CN 100398202C to prepare...

[0048] (1) Prepare 1200ml of copper and zinc mixed solution by mixing 117g of copper nitrate and 171g of zinc nitrate, and prepare 100ml of zinc and aluminum mixed solution by mixing 6g of zinc nitrate and 6g of aluminum nitrate. Add the zinc and aluminum mixed solution and sodium carbonate solution with a weight percentage of 15.7% in parallel to a neutralization tank with heat preservation and stirring for neutralization and aging. Control the neutralization temperature at about 80℃. Adjust the pH value to 7-8 by sodium carbonate solution. Then add the copper and zinc mixed solution and sodium carbonate solution with a weight percentage of 15.7% in parallel to the same neutralization tank for neutralization and aging under stirring. Wash four times with deionized water at 40-50℃. After drying the obtained filter cake, calcine it at 360-400℃ for 4-5 hours. Then add 2% of the total mass of the obtained substances to graphite to form a tablet to obtain catalyst sample CB-3.

[0049] Comparative Example 4

[0050] (1) Prepare a mixture of 100g aluminum nitrate, 1170g copper nitrate, 1100g zinc nitrate and 60g silica sol into 14000ml. Pump the aluminum-zinc-silicon mixed solution and a sodium carbonate solution with a weight percentage of 20% into the inlet of microreactor A respectively. After mixing and aging, obtain an aging solution. Control the temperature of microreactor A to about 80℃ and adjust the pH of the solution to 7-8.

[0051] (3) Filter the aging liquid, wash it with deionized water at 40-50℃, dry the obtained filter cake, calcine it at 360-400℃ for 4-5 hours, add the filter cake obtained in step (2), mix it evenly, and then add 2% of the total mass of the obtained substances to form graphite tablets to obtain catalyst CB-4.

[0052] Comparative Example 5

[0053] This example was prepared using the method described in Chinese Patent CN105727959B.

[0054] A 0.5 mol / L Cu, Zn, and Al nitrate solution and a 0.5 mol / L sodium carbonate solution were prepared, with a Cu:Zn:Al mass ratio of 30:6:1. The two solutions were pumped into a mixer, and the material was then introduced into a microchannel reaction tube with an inner diameter of 4 mm and held for 40 min in a constant temperature water bath at 60 °C. The collected product was washed, filtered, dried, calcined, and pressed into tablets to obtain methanol synthesis catalyst sample CB-5.

[0055] Comparative Example 6

[0056] The material ratios and processes used in this example are the same as those in Example 1, except that the filtrate obtained after filtration is not recycled.

[0057] (1) Prepare 2000ml of aluminum-zinc-silicon mixed solution by mixing 100g aluminum nitrate, 100g zinc nitrate and 60g silica sol. Add 120g ethylenediamine and 200g triethylene glycol to deionized water to prepare a precrystallization solution. Pump the aluminum-zinc-silicon mixed solution and the precrystallization solution into the inlet of microreactor A by weight respectively. After mixing, the precursor solution A1 is obtained. Control the temperature of microreactor A at about 80℃ and adjust the pH of the solution to 7-8.

[0058] (2) Prepare 13000 ml of copper-zinc mixed solution by mixing 1170 g of copper nitrate and 1000 g of zinc nitrate. Pump the mixed solution, precursor solution A1 and precipitant into the inlet of microreactor B respectively. After mixing, aging solution B1 is obtained. Control the neutralization temperature to about 80℃ and adjust the solution pH to 7-8.

[0059] (3) The aging liquid B is filtered and the filtrate is discharged directly without circulation. The filter cake is washed with deionized water at 40-50℃. After drying the obtained filter cake, it is calcined at 360-400℃ for 4-5 hours. Then, 2% of the total mass of the obtained material is added to graphite and pressed into tablets to obtain catalyst CA-1.

[0060] The physical properties of the prepared catalysts are listed in Table 1.

[0061] Table 1

[0062]

[0063] As can be seen from Table 1, the pore volume, specific surface area, and pore size of the examples are all greater than those of the comparative example. The larger specific surface area is beneficial to the dispersion of active copper metal, providing more active sites by exposing more active sites. The pore size of the catalyst in the examples is significantly higher than that of the catalyst in the comparative example. The larger pore size is beneficial to the diffusion of reactants inside the catalyst. When the catalyst pores are small, the trimers and heavy components in the reactants have large molecular weights, making it difficult to achieve effective hydrogenation.

[0064] The catalytic hydrogenation performance results of octenal in each example and comparative example are shown in Table 2.

[0065] The reduction was evaluated using a 300 mL fixed-bed hydrogenation evaluation apparatus under the following conditions: hydrogen reduction, reduction temperature 190 °C, and reduction time 6 h. The evaluation conditions were: industrial octenal as the feedstock, feed temperature 160 °C, hydrogen to octenal volume ratio 8000:1, and reaction space velocity 0.35 h⁻¹. -1 The reaction pressure is 0.45 MPa.

[0066] Table 2

[0067] Octenal conversion 99.99 99.98 99.98 97.57 97.57 97.60 98.59 98.66 Octyl alcohol selection 99.85 99.83 99.84 97.60 97.62 97.72 98.52 98.69

[0068] The above comparison shows that the catalyst prepared in this study has a higher octenal conversion rate (1.3–2.4%) and octanol selectivity (1.3–2.2%) than the comparative catalyst. This indicates that the catalyst prepared in this study has high activity selectivity.

[0069] The catalytic hydrogenation performance results of 2-propyl-2-heptenal in the examples and comparative examples are shown in Table 3.

[0070] Experimental process conditions: The raw material was self-made 2-propyl-2-heptenal; the feed temperature was 175℃; the volume ratio of hydrogen to 2-propyl-2-heptenal was 8000:1; and the reaction space velocity was 0.35 h⁻¹. -l The reaction pressure is 0.55 MPa.

[0071] Table 3

[0072] 2-Propyl-2 99.49 99.38 99.40 97.37 97.22 97.14 98.04 98.16 2-Propyl- 96.81 96.75 96.72 94.32 94.29 94.37 95.27 95.49

[0073] The above comparison shows that the catalyst prepared in this study has a higher conversion rate of 2-propyl-2-heptenal than the comparative catalyst by 1.2–2.3%, and a higher selectivity by 1.2–2.5%. Therefore, this invention is more suitable for the production of heavy alcohols.

[0074] Table 4 shows a comparison of the consumption of filtrate in processes with and without filtrate circulation.

[0075] Table 4

[0076] cycle benchmark benchmark benchmark benchmark benchmark benchmark Do not follow benchmark Baseline + 30% Baseline + 10% Baseline + 10% Baseline + 10% Baseline + 10%

[0077] The consumption of catalysts in the production process was compared by using filtrate recycling and non-recycling methods, as shown in Table 4. When the filtrate was recycled, the consumption of water, ethylenediamine and triethylene glycol was greatly reduced. The overall consumption of materials was reduced by recycling process. It is estimated that the production cost of catalysts can be reduced by more than 20% through filtrate recycling.

[0078] In summary, the method of the present invention improves the specific surface area of ​​the catalyst by combining pre-crystallization and co-precipitation, which is beneficial to the dispersion of copper on the support surface and thus improves the catalytic conversion efficiency of heavy aldehydes. At the same time, the recycling of the filtrate reduces wastewater discharge and lowers the catalyst preparation cost.

[0079] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an aldehyde hydrogenation catalyst, characterized in that, Includes the following steps: (1) A mixture of aluminum nitrate, zinc nitrate, silica sol, and deionized water was prepared. Ethylenediamine and triethylene glycol were added to deionized water to prepare a pre-crystallization solution. The mixture and the pre-crystallization solution were pumped into the inlet of the first microchannel reactor, and the precursor solution A was obtained by mixing and crystallizing. (2) The mixed solution of copper nitrate and zinc nitrate, precursor solution A and precipitant were pumped into the inlet of the second microchannel reactor for co-precipitation, and the aging solution B was obtained by mixing. (3) The aging liquid is filtered, and the filtered solution is recycled back to the second microchannel reactor. The filter cake is washed, dried, and the catalyst is formed. In step (1), the mixed crystallization temperature is 75-85°C, and the pH of the precursor solution A is 7-8; In step (2), the temperature of step (2) is controlled at 75-85°C, and the pH of the aging solution B is 7-8; In step (3), the drying conditions are: calcination at 360-400°C for 4-5 hours.

2. The preparation method according to claim 1, characterized in that, In step (3), the washing conditions are: the filter cake is washed with deionized water at 40-50°C; The molding conditions are as follows: the catalyst is obtained by adding graphite and pressing it into tablets.

3. The preparation method according to claim 1, characterized in that, The method is carried out in at least two microchannel reactors in series.

4. The preparation method according to claim 3, characterized in that, In step (3), the filtrate at the outlet of the second microchannel reactor is recycled back to the inlet of the second microchannel reactor.

Citation Information

Patent Citations

  • Process for preparing Cu-Zn-Al vapor hydroformylation catalyst and products therefrom

    CN100398202C

  • Aldehyde gas phase hydrogenation catalyst and preparation method thereof

    CN102350360A

  • A catalyst for the gas-phase hydrogenation of octenal to 2-ethylhexanol and its preparation method thereof

    CN105080549B

  • A method for preparing methanol synthesis catalysts using a microchannel reactor

    CN105727959B

  • Catalyst for preparing n-butyl alcohol by hydrogenation of n-butyl aldehyde and preparation method of catalyst

    CN108043411A